DDAH1 Promotes Cisplatin Chemoresistance in Patients with Locally Advanced Nasopharyngeal Carcinoma via the EGFR‐JAK2‐STAT3 Pathway - Jin‐Hao Yang; Li Yuan; Qiu‐Yan Chen; Kai‐Qi Lan; Liang‐Ji Li; Yu‐Chen Li; Xiao‐Yun Li; Xue‐Song Sun; Lin‐Quan Tang; Sai‐Lan Liu; Hai‐Qiang Mai (Advanced Science)
Abstract Cisplatin‐based induction chemotherapy (IC) improves survival in patients with locally advanced nasopharyngeal carcinoma (LANPC). However, ≈30% of patients with LANPC receiving IC develop chemoresistance, and 20% experience disease progression. The relation between chemoresistance and Dimethylarginine dimethylaminohydrolase‐1 (DDAH1) in NPC has not been mentioned in previous studies. To explore the regulatory mechanism and biological function of DDAH1 in cisplatin chemoresistance, NPC cell lines are subjected to overexpression and knockdown of DDAH1 in vitro, with findings further corroborated by in vivo chemosensitivity assays. The predictive value of DDAH1 expression is evaluated for survival and resistance to cisplatin‐based IC in a cohort of 339 patients with LANPC. Overexpression of DDAH1 in NPC cell lines increases cisplatin resistance both in vitro and in vivo through binding to the intracellular domain of epidermal growth factor receptor (EGFR), enhancing its dimerization and phosphorylation, thereby promoting the activation of the JAK2‐STAT3 pathway, which is dependent on EGFR and extracellular ligands and can be weakened by nimotuzumab. Clinically, DDAH1 positivity correlates with unfavorable 3‐year survivals. This study identified DDAH1 as a prognostic marker and a potential therapeutic target for nimotuzumab to overcome treatment failure and chemoresistance in LANPC and other EGFR‐positive cancers.